Temporal Trends in Outcomes of ST-Elevation Myocardial Infarction Patients With Heart Failure and Diabetes - Ali, Bassem; Dargham, Soha; Al Suwaidi, Jassim; Jneid, Hani; Abi Khalil, Charbel (Frontiers in Physiology, 2022)
Aims: We aimed to assess temporal trends in outcomes of ST-elevation myocardial infarction (STEMI) patients with diabetes and heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF) and compared both groups. Methods: Data from the National Inpatient Sample was analyzed between 2005 and 2017. We assessed hospitalizations rate and in-hospital mortality, ventricular tachycardia (VT), ventricular fibrillation (VF), atrial fibrillation (AF), cardiogenic shock (CS), ischemic stroke, acute renal failure (ARF), and revascularization strategy. Socio-economic outcomes consisted of the length of stay (LoS) and total charges/stay. Results: Hospitalization rate steadily decreased with time in STEMI patients with diabetes and HFrEF. Mean age (SD) decreased from 71 ±12 to 67 ±12 (p<0.01), while the prevalence of comorbidities increased. Mortality was stable (around 9%). However, VT, VF, AF, CS, ischemic stroke, and ARF significantly increased with time. In STEMI patients with HFpEF and diabetes, the hospitalization rate significantly increased with time while mean age was stable. The prevalence of comorbidities increased, mortality remained stable (around 4%), but VF, ischemic stroke, and ARF increased with time. Compared to patients with HFrEF, HFpEF patients were two years older, more likely to be females, suffered from more cardio-metabolic risk factors, and had a higher prevalence of cardiovascular diseases. However, HFpEF patients were less likely to die (adjusted OR = 0.635 [0.601-0.670]) or develop VT (adjusted OR= 0.749 [0.703-0.797]), VF (adjusted OR= 0.866 [0.798-0.940]), ischemic stroke (adjusted OR = 0.871 [0.776-0.977]), and CS (adjusted OR= 0.549 [0.522-0.577]), but more likely to develop AF (adjusted OR=1.121 [1.078-1.166]). HFpEF patients were more likely to get PCI but less likely to get thrombolysis or CABG. Total charges per stay increased by at least 2-fold in both groups. There was a slight temporal reduction over the study period in the LoS of the HFpEF Conclusion: While hospitalizations for STEMI in patients with diabetes and HFpEF followed an upward trend, we observed a temporal decrease in those with HFrEF. Mortality was unchanged in both HF groups despite the temporal increase in risk factors. Nevertheless, HFpEF patients had lower in-hospital mortality and cardiovascular events, except for AF.